2013
DOI: 10.1177/2047487313516563
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime risk for cardiovascular disease in a Chinese population: the Chinese Multi–Provincial Cohort Study

Abstract: During follow-up years from 1992 to 2010, 1,280 participants developed acute CVD events and 1,401 died. The lifetime CVD risk, up to age 80 for men and women at age 35, were 24.4% and 20.2% respectively. A very low lifetime risk was found in individuals with an optimal profile of risk factors which modified the effect of aging. By contrast, with two or more high risk factors the lifetime risk up to age 80 reached 51.1% for men and 38.6% for women at age 35. The integrated status of major CVD risk factors can d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 18 publications
(18 reference statements)
1
44
1
Order By: Relevance
“…The largest cohort began at 1992 and included 16 811 participants aged 35–64 years who were free of CVD at baseline. The detailed methodology of the sampling has been described in previous publications [15,16]. From 1996 to 1999, 3129 participants aged 35–64 years who were free of CVD at baseline were added, and 2013 participants (45.7% older than 60 years) aged 35–84 years and free of CVD at baseline were added in 2004 to increase the sample size of elderly people.…”
Section: Methodsmentioning
confidence: 99%
“…The largest cohort began at 1992 and included 16 811 participants aged 35–64 years who were free of CVD at baseline. The detailed methodology of the sampling has been described in previous publications [15,16]. From 1996 to 1999, 3129 participants aged 35–64 years who were free of CVD at baseline were added, and 2013 participants (45.7% older than 60 years) aged 35–84 years and free of CVD at baseline were added in 2004 to increase the sample size of elderly people.…”
Section: Methodsmentioning
confidence: 99%
“…Blood pressure (BP) is one of the most important modifiable risk factors for cardiovascular diseases (CVD) in China [1]. Mean national consumption is more than 12 g/day of salt (sodium chloride), a level higher than in most other countries [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is one of the most common chronic noncommunicable diseases and is also a major risk factor for cardiovascular disease (CVD) 9 in China and worldwide (1,2). Numerous studies over the past couple of decades have shown that dietary sodium intake is positively associated with blood pressure (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been proposed for estimating 24-h urinary sodium 1 Supported by the China-Australia Health and HIV/AIDS program (CAHHF; grant HSS107). 2 Supplemental Figures 1-3 and Supplemental Tables 1-3 are available from the "Online Supporting Material" link in the online posting of the article and from the same link in the online table of contents at http://ajcn. nutrition.org.…”
Section: Introductionmentioning
confidence: 99%